Identificação de mecanismos de desgaste através de sinais de emissão acústica aplicada ao deslizamento entre dutos flexíveis e liners - Suriani, Marco Aurélio Moura (2014)
The driving of oil in deep water oil exploration is performed commonly by risers, which are coated externally by polyamide. At the point where these pipes connect to the platform, they slide against a liner, which is supposed to wear in the place of the flexible riser pipe. The purpose of this work was to investigate the Acoustic Emission (AE) potential in monitoring the wear between the riser pipe and the liner. This investigation was performed through acquisitions of AE in a full-scale test, simulating the sliding process between the two mentioned surfaces. The methods of signals analysis were its RMS value and their peak frequencies. Preliminarily, small-scale tests were carried out with the aim of studying the acoustic signals that emanate from the wear. First of all tests were carried out in a linear sclerometry sample of nickel chemically coated steel and in samples of different polymers, using different indenters to force changes in the mechanisms of wear. These tests have shown that the RMS value of AE is sensitive to the presence of cracks, as well as stick-slip events, and indicated that cracking generates acoustic signals with peak frequencies in the range of 0 to 50 kHz and stick-slip generates signals with peak frequencies around 85 kHz. We also carried out abrasive wear tests using carbon steel pins, polyamide and polyurethane against abrasive paper. In these tests, it was found mainly abrasive wear by microplowing and microcutting that generate acoustic signals with several peaks with frequencies between 25 and 225 kHz. In the small-scale sliding wear tests of between polyamide and polyurethane, using a reciprocating pin-on-flat configuration, was observed predominantly Schallamach waves and abrasion. The corresponding acoustic waves showed low frequencies and low amplitudes, with values close to 50 kHz, similar to those found in the linear sclerometry and abrasive tests. Finally, the test was carried out in full-scale tribometer but the AE acquisitions did not showed the wear events occurring between the samples. It is believed that this happened because the sensor was relatively distant from the region of wear events and because the polyurethane damping effect is quite high. However, it is concluded that the method of AE has the potential to accomplish the liner monitoring if the AE sensor is placed closer to the wear events source.